India Turkey Defense Relations: Prospects and Challenges - javed zafar (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
In the post-Cold War scenario, the world is changing geopolitically. Old alliances are creaking, and new ones are being made. India and Turkey are emerging as the world's middle powers. Turkey and India both have a historical relationship. Both countries are part of the G-20. In the post-Cold War era, both countries are looking for opportunities for cooperation. This paper discusses bout changing global scenario and Turkey and India’s strategic requirements. The paper also discusses the different strengths of both countries. This paper also analyzes the historical background of their defense cooperation. The paper also talks about the current status of defense cooperation. The paper examines areas of future cooperation and the challenges they pose.